2011
DOI: 10.1111/j.1365-2672.2011.05145.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of exoinulinase gene from Penicillium janthinellum strain B01 and its high-level expression in Pichia pastoris

Abstract: Aims:  The aim of this study is to improve exoinulinase production by expression of a cloned exoinulinase gene inuA1 (GenBank accession no. ) from Penicillium janthinellum strain B01 in Pichia pastoris. Methods and Results:  A full‐length cDNA of exoinulinase gene (inuA1) was cloned from P. janthinellum strain B01 using RACE PCR. An open reading frame (ORF) of 2115 bp is interrupted by a single intron of 67 bp. The fragment encodes a signal peptide with 20 amino acids and a mature protein with 684 amino acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…a-factors) as well as more detailed studies on the cellular localization of the inulinase protein in yeast. Surprisingly, although the expression level of inulinase in S. cerevisiae was less than that in Picha pastoris reported earlier (Wang et al 2011), it greatly enhanced the production of ethanol from inulin, as described further in the text.…”
Section: Construction Of the 18srdna Integration Vectormentioning
confidence: 63%
See 3 more Smart Citations
“…a-factors) as well as more detailed studies on the cellular localization of the inulinase protein in yeast. Surprisingly, although the expression level of inulinase in S. cerevisiae was less than that in Picha pastoris reported earlier (Wang et al 2011), it greatly enhanced the production of ethanol from inulin, as described further in the text.…”
Section: Construction Of the 18srdna Integration Vectormentioning
confidence: 63%
“…Previously, it was reported that the inulinase activity of a yeast transformant with an inulinase gene integrated into its genome remained very stable during five sequential batch cultivations in a nonselective medium. In contrast, the inulinase activity of a transformant carrying the same gene in a plasmid (Ycplacc33) decreased gradually Wang et al 2011). The integration strategy used in the present study not only facilitates stable recombination of the heterologous gene, but also increases the possibility of integrating multiple copies (Figure 1) contained the constitutive promoter PGK1 (782 bp) and the effective terminator CYC1 (249 bp).…”
Section: Construction Of the 18srdna Integration Vectormentioning
confidence: 83%
See 2 more Smart Citations
“…For example, the molecular masses of 9 characterized inulinases are over the range of 49. 8 24,26 and the exo-inulinase from P. janthinellum B01 is also inhibited by 1 mM Na C . 24 Compared with the above exo-inulinases, InuAHJ7 is different: the exo-inulinase has a molecular mass of 95.1 kDa and shows tolerance to 3.0%-20.0% (w/v) Na C and 1.0 and 10.0 mM Zn 2C and Pb 2C .…”
Section: Discussionmentioning
confidence: 99%